Diary of Richard Cocks, Cape-Merchant in the English Factory in Japan 1615-1622 with Correspondence : Volume II. - Thompson, Edward Maunde (Oxford : Hakluyt Society, 2010)
Continues from First Series 67, with the years 1618-1622, .together with Cocks's correspondence with the East India Company and others. This is a new print-on-demand hardback edition of the volume first published in 1883.
Cover -- DIARY OF RICHARD COCKS -- 1618 -- JANUARY -- FEBRUARY -- MARCHE -- APRILL -- MAY -- JUNE -- JULY -- AUGUST -- SEPTEMBER -- OCTOBER -- NOVEMBER -- DECEMBER -- 1619 -- JANUARY -- 1620 -- DECEMBER -- 1621 -- JANUARY -- FEBRUARY -- MARCHE -- APRILL -- MAY -- JUNE -- JULY -- AUGUST -- SEPTEMBER -- OCTOBER -- NOVEMBER -- DECEMBER -- 1622 -- JANUARY -- FEBRUARY -- MARCH -- APPENDIX -- CORRESPONDENCE.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Great Britain--Commerce--Japan--Early works to 1800.; Electronic books